Michigan Focused Biomass Waste Circular Economy Case Studies - Claire O'Dea; Brianna Fogal; Angie Sillah; Sara Soderstrom (Urban Food Systems Symposium, 2024)
This project developed two case studies to demonstrate a biomass waste circular economy with a focus on food and agriculture waste in Michigan. Each case study was chosen as a representation of the potential pathways for urban food and agriculture waste to be recycled throughout the system. The first case study examines food waste taken from the University of Michigan’s two major athletic and event complexes, Michigan Stadium and Crisler Center, to use as input for an anaerobic digester for the campus to produce biogas and liquid digestate. To make the purchase of an anaerobic digester beneficial to the university, a minimum of four years of use will be required when selling the liquid digestate and utilizing the energy output. The second case study examines soybean and cherry pit waste from Michigan farms to act as input for Sustainable Aviation Fuel (SAF) for the Detroit Wayne County Airport (DTW). Each agriculture waste source was chosen based on the production quantity throughout the state. Michigan is the number one producing state of tart cherries and a major producer of soybeans. This method of using agricultural waste does not become beneficial for the immediate future due to the price of SAF technology; however, the combination of cherry pit and soybean waste and production can produce 93 days of fuel for DTW, which will significantly reduce the carbon footprint of the airport. The goal of this project was to address the growing waste crisis and establish solutions that are beneficial to both communities and the environment. Our work emphasizes the need for systemic changes in how waste is approached and highlights the positive potential outcomes achievable through the effective utilization of biomass waste as a resource.
Keywords: Agricultural Waste; Anaerobic Digestion; Athletic Facilities; Food Waste; Sustainable Aviation Fuel